Interventional management for chronic pain - Dessy R Em.ril (Universitas Syiah Kuala, 2009)
Abstract. Chronic pain is a common clinical condition affecting the quality of life of the population. This article aims to review the interventional options for chronic pain based on literature researches. Multiple searches using Medline were carried out and additional searches were made using reference lists of published papers and book chapters. The article discussed procedures ranging from selective nerve root or zygapophyseal (facet) joint block with local anaesthetics to irreversible neurodestruction with radiofrequency energy or neurolytic agents and epidural injection. Other techniques include intraspinal delivery of analgesics. · There is evidence that these interventional procedures are valuable both diagnostically and therapeutically. (JKS 2009; 3:139-144)Key words: spinal pain, neurophathicpain, intervention Abstrak. Nyeri kronik adalah kondisi yang sering dijumpai ciao mempengaruhi kualitas hidup penderitanya. Artikel ini bertujuan untuk rnembahas secara umum tentang penatalaksanaan intervensi yang bersifat minimal invasive pada nyeri kronik berdasarkan review terhadap berbagai literature. Dalam makalah ini didiskusikan tentang berbagai prosedur mulai dari prosedur dasar hingga yang lanjut. Sebagian penelitian membuktikan bahwa tindakan intervensi pada nyeri kronik memberikan manfaat baik secara terapetik maupun diagnostic. (JKS 2009; 3: 139-144) Kata kunci: nyerispinal, nyeri neuropatik, tindakan intervensi